Monetary liquidity and the bubbles in the U.S. housing market - Tsai, I-Chun (International Journal of Strategic Property Management, 2015)
Extant studies indicate that the excessive easing of monetary supplies can result in surplus liquidity, which can consequently facilitate the formation of asset bubbles. This study references data on house prices in the U.S. from January 1991 to August 2012 to explore the correlations between monetary liquidity and house price bubbles in the U.S. housing market. Fluctuations in house prices are classified as related to either fundamentals (the mean reversion behavior and responses to information of the current period) or bubbles (self-related behavior). Results show a significant correlation between the formation of housing bubbles and monetary supplies. Long-term easing of monetary supplies can cause housing marketing returns to deviate from fundamentals, which then results in an increase in continuous fluctuations in house prices and the likelihood of the formation of house price bubbles. First Publish Online: 1 Apr 2015